2001
DOI: 10.2494/photopolymer.14.677
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development in Photosensitive Polyimide (PSPI)

Abstract: Photosensitive polyimides (PSPIs) are attracting much attention as an insulating materials for microelectronic applications. PSPIs can be directly patterned, simplify processing steps and do not need a photoresist to be used in the micro-lithographic stage, nor a toxic etchant. This review introduces the recent development of PSPIs with emphasis placed on the chemistry responsible for images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Thermally stable and photosensitive polymers, especially photosensitive polyimides (PSPIs) (18)(19)(20)(21)(22) and polybenzoxazoles (PSPBOs) (27)(28)(29)(30)(31)(32), are widely used as protection and insulation layers of very-large-scale integrationcircuit multichip modules for computers. Even though PSPIs and PSPBOs have greatly enhanced the progress of microelectronics so far, more technological innovations involving simpler processes and more valuable properties such as transparency, low dielectric constant, higher sensitivity, low temperature cyclization, etc.…”
Section: The Concept Of Chemical Amplification Was Proposed By Ito Wmentioning
confidence: 99%
“…Thermally stable and photosensitive polymers, especially photosensitive polyimides (PSPIs) (18)(19)(20)(21)(22) and polybenzoxazoles (PSPBOs) (27)(28)(29)(30)(31)(32), are widely used as protection and insulation layers of very-large-scale integrationcircuit multichip modules for computers. Even though PSPIs and PSPBOs have greatly enhanced the progress of microelectronics so far, more technological innovations involving simpler processes and more valuable properties such as transparency, low dielectric constant, higher sensitivity, low temperature cyclization, etc.…”
Section: The Concept Of Chemical Amplification Was Proposed By Ito Wmentioning
confidence: 99%
“…Accordingly, low internal stress also required for dielectric layer materials. As dielectric layer materials, polyimide and polybenzoxazole are widely used, because of its excellent heat resistance, chemical resistance, and high mechanical properties [1]. In our previous study, we showed polyimide is more suitable than polybenzoxazole from reliability for thermal cycle test viewpoint by experiment and finite element analysis (FEA) because of its good elongation at -55deg.C and the fatigue properties [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In semiconductor field, photosensitive PI (PSPI) is used as passivation layer for chip surface protection, alpha particle shielding layer, stress buffer layer and interlayer dielectrics for re-distribution layer of semiconductor devices [1].…”
Section: Introductionmentioning
confidence: 99%